2017
DOI: 10.1038/celldisc.2017.44
|View full text |Cite
|
Sign up to set email alerts
|

A role for ErbB signaling in the induction of reactive astrogliosis

Abstract: Reactive astrogliosis is a hallmark of many neurological disorders, yet its functions and molecular mechanisms remain elusive. Particularly, the upstream signaling that regulates pathological responses of astrocytes is largely undetermined. We used a mouse traumatic brain injury model to induce astrogliosis and revealed activation of ErbB receptors in reactive astrocytes. Moreover, cell-autonomous inhibition of ErbB receptor activity in reactive astrocytes by a genetic approach suppressed hypertrophic remodeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 82 publications
(133 reference statements)
1
37
0
Order By: Relevance
“…Furthermore, they induce the release of neuroregulins, mediators of their biological activity through the binding of the receptor tyrosine kinases that encloses the ErbB genes [ 56 , 57 ]. The ErbB receptor family is an important regulator of oligodendrogenesis, myelination, and serotonin brain levels [ 58 ]; interestingly, we found that the ErbB signalling was the second most significant canonical pathway resulting from our data. On the other hand, a Gene Ontology (GO) term enrichment analysis showed that all the DE miRNAs, TFs, and their target genes were involved in important immune functions and in the maintenance of neuronal homeostasis.…”
Section: Discussionmentioning
confidence: 57%
“…Furthermore, they induce the release of neuroregulins, mediators of their biological activity through the binding of the receptor tyrosine kinases that encloses the ErbB genes [ 56 , 57 ]. The ErbB receptor family is an important regulator of oligodendrogenesis, myelination, and serotonin brain levels [ 58 ]; interestingly, we found that the ErbB signalling was the second most significant canonical pathway resulting from our data. On the other hand, a Gene Ontology (GO) term enrichment analysis showed that all the DE miRNAs, TFs, and their target genes were involved in important immune functions and in the maintenance of neuronal homeostasis.…”
Section: Discussionmentioning
confidence: 57%
“…Interestingly, we have also previously detected a post-traumatic contralateral upregulation of S100A4 19 , both effects most probably following the spreading astrocytic activation, which occurs in focal brain injuries 49 , 50 and was also observed in our cryogenic lesion model 19 . Moreover, as it was recently demonstrated in a mouse brain injury model and human brain astrocytes, spreading astroglyosis can affect and be reciprocally regulated by the activation of ErbB receptors in reactive astrocytes 51 , 52 . Since S100A4 can be released from stressed astrocytes 19 and upregulate ErbB4 mRNA in cultured neurons (Fig 2 C), S100A4 present in the CL hemisphere of WT animals with brain injury might directly and/or by affecting astroglyosis modulate contralateral ErbB4 expression.…”
Section: Discussionmentioning
confidence: 85%
“…The EGFR family (EGFR also known as HER) is a subset of receptor tyrosine kinases that activate and regulate diverse processes, including cell survival, proliferation, differentiation, and migration . It has been shown to be activated in many epithelial cancers such as colorectal, breast, and lung cancers .…”
Section: Discussionmentioning
confidence: 99%